Organizational Climate as an Intervening in the Relationship of Job Demand Resources and Person Organization fit to Employee Engagement - Fahmi Abdullah (Enrichment : Journal of Management, 2022)
Teachers who are an important pillar in an educational institution should receive facilities and fulfillment of needs in order to create comfort and foster loyalty in attachment to an organization or educational institution. The purpose of this research is to find out and explain how far the influence of Job Demand Resources and Person Organization Fit on Employee Engagement with Organization Climate as an Intervening variable. The method used in this research is quantitative with the teacher as the research sample. The results of this study are Job Demand Resources and Person Organization Fit have an influence on Employee Engagement. Job Demand Resources have no influence on Organization Climate while Person Organization Fit has an influence on Organization Climate and Organization Climate has no effect on Employee Engagement. Organization Climate is unable to mediate Job Demand Resources and Person Organization Fit.